Middle Management and School Autonomy in Italy: The Case of Teachers as «Instrumental Functions» - Lorena Pirola (LED Edizioni Universitarie, 2015)
An autonomous school is a complex community. An organizational structure with different roles or «functions» is required in order to achieve its cultural and educational project, and to provide an answer to social needs. Middle professional workers with organizational, planning and coordination duties are expected to support the work of the head teacher and teachers. This article focuses on the «Instrumental Functions» whose origin can be traced back to «Objective Functions» and «System Figures». It also focuses on the teachers who fulfil these functions and who are identified by them. A historical, political analysis highlights that, unlike other countries, there are no proper middle management roles in Italian schools. In fact, besides teaching, Italian teachers are only assigned temporary functional duties. An exploratory survey underscores the importance of the «Instrumental Functions» and identifies their vulnerability: the fragmentation of resources and high staff turnover. What stands out is the demotivation of teachers in carrying out this role, due to an uncertain institutional framework and the lack of training. The risk is that «Instrumental Functions» are considered to be just like any other extra teaching tasks, with the consequent loss of the unique features of these functions. This article concludes that encouraging this kind of professionalism not only allows the organizational development of schools, but also paves the way for teachers' professional development.